Implementasi Kebijakan Penataan Kependudukan dalam Penonaktifan Data Kependudukan di Kota Padang Panjang - Latifa Hadi; Aldri Frinaldi (Policy, Law and Political Research Center, 2022)
Population data is an important pillar by the government in distributing community welfare programs. There is still a lack of awareness of non-domicile residents who are registered as permanent residents of the city of Padang Panjang and have a Family Card as well as the difficulty of collecting data on non-domicile residents in the covid-19 era. Thus hindering the implementation of Padang Panjang Perwako. No. 65 of 2020 concerning population structuring in the city of Padang Panjang which has the consequence of deactivating population data. Thus, the purpose of this study is to analyze the processes, efforts and constraints of the implementation of population policies in deactivating population data in the city of Padang Panjang. The research method used is descriptive qualitative method with MDAP data analysis techniques. The results of the study explain that population structuring policies are still not fully effective due to uneven policy socialization, lack of RT commitment to policies, and difficulty in verifying the existence of non-domicile residents.